THE EFFECT OF ENTREPRENEURSHIP KNOWLEDGE, PERSONALITY AND FAMILY ENVIRONMENT ON STUDENT ENTREPRENEURIAL INTERESTS - Anjelia Zahra Rhamanda; Marsofiyati; Eryanto, Henry (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
The purpose of this study was to determine the effect of entrepreneurial knowledge, personality and family environment on the entrepreneurial interest of students at SMK Negeri 22 Jakarta. This research is a causal associative research with a quantitative approach and uses a survey method. The population in this study were students of SMK Negeri 22 Jakarta. The sampling technique used purposive sampling technique with certain considerations so that the population in this study was 313 students and the sample was 170 students. The data analysis technique used in this study uses Structural Equation Modeling Partial Least Squares (SEM-PLS) which is calculated using SmartPLS software. The results of this study indicate that entrepreneurial knowledge has a positive and significant effect on students' interest in entrepreneurship, personality has a positive and significant effect on students' interest in entrepreneurship and the family environment has a positive and significant effect on interest in entrepreneurship and knowledge of entrepreneurship, personality and family environment on interest in entrepreneurship. Tujuan dari penelitian ini yaitu untuk mengetahui pengaruh pengetahuan kewirausahaan, kepribadian dan lingkungan keluarga terhadap minat berwirausaha siswa SMK Negeri 22 Jakarta. Penelitian ini merupakan penelitian berbentuk asosiatif kausal dengan pendekatan kuantitatif dan memakai metode survey. Populasi pada penelitian ini merupakan siswa SMK Negeri 22 Jakarta. Teknik penentuan sampel menggunakan teknik purposive sampling dengan pertimbangan tertentu sehingga populasi dalam penelitian ini sebanyak 313 siswa serta sampel berjumlah 170 siswa. Teknik analisis data yang digunakan pada penelitian ini menggunakan Structural Equation Modeling Partial Least Squares (SEM-PLS) yang dihitung menggunakan software SmartPLS. Hasil dari penelitian ini menunjukkan bahwa pengetahuan kewirausahaan berpengaruh positif dan signifikan terhadap minat berwirausaha siswa, kepribadian berpengaruh positif dan signifikan terhadap minat berwirausaha siswa dan lingkungan keluarga berpengaruh positif dan signifikan terhadap minat berwirausaha serta pengetahuan kewirausahaan, kepribadian dan lingkunga keluarga terhadap minat berwirausaha.